Identification, characterization, and stabilization of the deamidation degradation of recombinant human tumor necrosis factor-α. (February 2017) - Yin, Shuang; Zhang, Chun; Li, Zenglan; Wang, Qi; Shi, Hong; Yu, Rong; Liu, Yongdong; Su, Zhiguo
Graphical abstract: Highlights: The Asp34 and Asp 39 residues are found to deamidate in tumor necrosis factor-α. Asp34 deamidation causes notable decrease of bioactivity of tumor necrosis factor-α. Glycerol has a good capacity for retarding deamidation. Abstract: A kind of degradation characterized by an increase in overall negative charge in both native polyacrylamide gel electrophoresis analysis and high-performance strong anion exchange analysis was observed during the purification process of recombinant human tumor necrosis factor-α (TNF-α). Liquid chromatography coupled with tandem mass spectrometry was adopted to further analyze this degradation, and the result demonstrated that suspected deamidation occurred at N39 and N34 residues. To investigate the effects of these deamidation degradations on TNF-α, we substituted corresponding asparagine residues with aspartic acid residues. High-performance size-exclusion chromatography, circular dichroism, and fluorescence spectrometry analysis revealed that the advanced structures of TNF-α could not be obviously changed by these substitutions. Differential scanning calorimetry analysis indicated that deamidation led to decreased thermal stability, and two mutants (N34D, N34DN39D) both possessed two Tm. L929 cell cytotoxic activity implied that N39 residue deamidation caused only a minor bioactivity loss, whereas N34 residue deamidation led to a bioactivity loss of four orders of magnitude. To alleviate the degradation during the purification process, we screened nine excipients and found that glycerol could notably ameliorate this degradation and provide a compromise strategy for the recombinant human TNF-α protein during purification process and formulation development.